Hereditary Hypercalcemia Caused by a Homozygous Pathogenic Variant in the CYP24A1 Gene: A Case Report and Review of the Literature - Daniele Cappellani; Alessandro Brancatella; Martin Kaufmann; Angelo Minucci; Edda Vignali; Domenico Canale; Elisa De Paolis; Ettore Capoluongo; Filomena Cetani; Glenville Jones; Claudio Marcocci (Case Reports in Endocrinology)
Introduction. Loss of function mutations of CYP24A1 gene, which is involved in vitamin D catabolism, cause vitamin D-mediated PTH-independent hypercalcemia. The phenotype varies from life-threatening forms in the infancy to milder forms in the adulthood. Case Presentation. We report a case of a 17-year-old woman with a history of nephrolithiasis, mild PTH-independent hypercalcemia (10,5mg/dL), and high serum 1,25(OH)2D concentrations (107pg/mL). Other causes of hypercalcemia associated with the above biochemical signature were excluded. Family history revealed nephrolithiasis in the sister. Blood testing in first-degree relatives showed serum PTH in the low-normal range and 1,25(OH)2D at the upper normal limit or slightly elevated. The CYP24A1 gene analysis revealed a known homozygous loss-of-function pathogenic variant (c.428_430delAAG, rs777676129, p.Glu143del). The panel of vitamin D metabolites evaluated by liquid chromatography showed the typical profile of CYP24A1 mutations, namely, low 24,25(OH)2D3, elevated 25(OH)D3:24,25(OH)2D3 ratio, and undetectable 1,24,25(OH)3D3. The parents and both the siblings harbored the same variant in heterozygosis. We decided for a watchful waiting approach and the patient remained clinically and biochemically stable over a 24-month followup. Conclusion. CYP24A1 gene mutations should be considered in cases of PTH-independent hypercalcemia, once that more common causes (hypercalcemia of malignancy, granulomatous diseases, and vitamin D intoxication) have been ruled out.